Coronavirus Disease 2019: Where are we and Where are we Going? Intersections Between Coronavirus Disease 2019 and the Heart - Emilia D’Elia (Radcliffe Medical Media, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19), which has become a pandemic affecting every country in the world. In the province of Bergamo, Italy, more than 2,200 cases of COVID-19 have been reported, which include more than 300 deaths. Most hospitalisations have been at the Papa Giovanni XXIII Hospital. This has imposed a significant burden on our hospital in terms of healthcare personnel, dedicated spaces (including intensive care areas) and time spent by clinicians, who are committed to assisting COVID-19 patients. In this short expert opinion, the authors will focus on new insights related to COVID-19 and the cardiovascular system, and try to investigate the grey areas and uncertainties in this field.